Membangun Kesadaran Religius Melalui Maghrib Tilawah di Masjid At-Takwa Desa Baru Kabupaten Asahan - Alpi Robiah Al Adwiyah Nasution; Robie Fanreza (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2024)
This community service program aims to build religious awareness in the community through Maghrib Tilawah activities at the At-Takwa Mosque, Baru Village, Asahan Regency. This program focuses on children and adolescents, with the aim of getting them used to reading the Qur'an after Maghrib prayers. In this activity, participants are accompanied by ustadz and Community Service (KKN) students who provide guidance on tajwid and correct reading. In addition to improving the ability to read the Qur'an, this activity also teaches Islamic moral values ​​and behavior through short lectures delivered after the tilawah session. Based on the results of observations, this activity succeeded in attracting the active participation of around 30 participants each night. The positive impact can be seen from the increase in the ability to read the Qur'an and changes in the behavior of participants who become more religious. Some challenges in implementing the program include fluctuations in the number of participants and the need for extra guidance for children who still have limitations in reading the Qur'an. With continuous evaluation and adjustment, this program is expected to continue to contribute to increasing religious awareness in the community, as well as creating a strong foundation for the future Qur'anic generation.